THE ROLE OF VILLAGE REGULATIONS (PERDES) IN SUPPORTING SUSTAINABLE DEVELOPMENT GOVERNANCE AT THE LOCAL LEVEL: A CASE STUDY IN PAKAM VILLAGE, MEDANG DERAS DISTRICT, BATU BARA REGENCY - Tia Indria; Budiman Purba; Fandi Alfiansyah Siregar (Universitas Dharmawangsa Medan, 2026)
This study aims to analyse the role of Village Regulations (Perdes) in supporting sustainable development governance at the local level, particularly in Pakam Village, Medang Deras Sub-district, Batu Bara Regency. Sustainable development at the village level requires a balance among economic, social, and environmental dimensions, and its implementation depends on a strong and participatory local regulatory framework. As a legal product of the village, Perdes plays a strategic role in directing development, defining implementation mechanisms, and articulating community involvement in development processes. The study uses a qualitative descriptive approach with a case-study method. Data were collected through in-depth interviews, participatory observation, and documentation of Perdes and village development activities. Informants included village officials, the Village Consultative Body (BPD), village facilitators, community leaders, and beneficiary residents. The data were analysed using the interactive model of Miles and Huberman through data reduction, data presentation, and conclusion drawing. The findings show that Perdes in Pakam Village functions as a normative foundation for guiding sustainable development governance. The effectiveness of Perdes, however, is influenced by the level of community participation, the capacity of village officials, and the consistency of monitoring and policy implementation. The study concludes that Perdes is not only an administrative instrument but also a strategic means to realise sustainable village development, provided it is supported by participatory drafting, accountable implementation, and effective oversight. Keywords: Village Regulation; Local Governance; Sustainable Development; SDGs Desa; Pakam Village